2020
DOI: 10.1097/xce.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers for subtle myocardial involvement in type I diabetes mellitus

Abstract: Background Evaluation of certain biomarkers could be used to predict left ventricular (LV) and right ventricular (RV) function impairment in children with type 1 diabetes mellitus. The aim of this study was to determine the best cardiac biomarker for prediction of diabetic cardiomyopathy. Methodology This study was designed as case-control study. A total of 55 children with type 1 diabetes mellitus (group/G1) and 55 healthy controls (G2) were subjected to echocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus is a chronic disorder that is characterized by insulin resistance and hyperglycemia and may lead to metabolic syndrome. [ 17 ] The elderly patients with diabetes frequently lead to f abnormal glucose metabolism and diabetic complications including nephropathy in these patients. [ 18 ] Resveratrol has antidiabetic properties, and few reports investigate its safety and efficacy in the treatment of elderly patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a chronic disorder that is characterized by insulin resistance and hyperglycemia and may lead to metabolic syndrome. [ 17 ] The elderly patients with diabetes frequently lead to f abnormal glucose metabolism and diabetic complications including nephropathy in these patients. [ 18 ] Resveratrol has antidiabetic properties, and few reports investigate its safety and efficacy in the treatment of elderly patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The focal point of the present study is our observation of marked degeneration and vacuolation of myocardial fibers in untreated diabetic rats, which positively correlated with elevated levels of cardiac damage markers such as troponin I (cTnI), creatine kinase myoglobin band (CK-MB) and brain natriuretic peptide (BNP) in plasma and heart tissue. cTnI and CK-MB are powerful biomarkers for sensitive and specific detection of cardiomyopathies such as DCM or cardiac injury from various causes while BNP is a non-specific but sensitive biomarker for predicting cardiac dysfunction including DCM ( Atabek et al, 2004 ; Korraa et al, 2012 ; El-Saiedi et al, 2020 ; Ajiboye et al, 2021 ). Thus, increased levels of these biomarkers predict the risk of cardiomyocyte death and subsequent adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the study by Liu et al showed that in neonatal rat cardiomyocytes, pioglitazone prevented the increase in CT-l expression in high-glucose, high-insulin-induced hypertrophic cardiomyocytes, indicating that CT-1 is a major regulator of fat and glucose metabolism with potential applications in the treatment of obesity and IR [ 121 ]. 3D speckle-tracking echocardiography and tissue Doppler imaging were used in a clinical trial by Sonia et al [ 122 ], who compared 55 children with type 1 diabetes to 55 healthy controls and found that diabetic patients exhibited right ventricular and left ventricular systolic-diastolic dysfunction compared to controls. The best predictor of left ventricular systolic dysfunction was CT-1 (sensitivity: 69%).In an observational study of 93 patients with T2DM, Gamella-Pozuelo [ 123 ] discovered that diabetic patients had significantly higher plasma CT-1 levels and were more likely to have ventricular hypertrophy.…”
Section: Mechanisms Contributing To the Development Of Dcmmentioning
confidence: 99%